PENERAPAN METODE PROBLEM POSSING PADA PROGRAM KEAKSARAAN USAHA MANDIRI DI PKBM - Durotul Yatimah (Jurnal Ilmiah Visi, 2012)
In general, there are several problems in the practice of functional literacy instruction. In the independent business literacy instruction at Community Learning Activity Center, Kemayoran, Central Jakarta, verbal method is the only method used and not enriched with other methods making the learners bored and not motivated to learn. To solve this problem, this research implemented problem possing method at the Center as from January through April 2012. This method enables the learner to identify and formulate problems and search for the alternative solutions. This research employed pra-experiment with One Group Pretest-Posttest Design approach. The research findings indicated problem possing method successfuly incrcreased the learners’s motivation and the learning outcome could improve the learners’ aditional income and family welfare.